Fiscal and debt sustainability in a federal structure: The case of Assam in North East India - Parag Dutta (Romanian Journal of Fiscal Policy (RJFP), 2014)
While containing deficits and public debt at sustainable level is a matter of concern for all the states in India, their heterogeneity in terms of size, level of income, fiscal position and the ability to raise resources calls for individual analysis of the issue of fiscal sustainability of a particular state. Assam in northeast India has been experiencing the problem of fiscal instability since 1990s due mainly to the rise in public debt and fiscal deficit. A relatively better fiscal position in the earlier part of the present century is followed by rising public debt and deficits in recent years. Based on secondary data, the present study is an attempt to analyse the fiscal and debt sustainability of the state during 1991 - 2010. The study finds that a higher proportion of revenue deficit in fiscal deficit has resulted in fiscal instability in some years during the study period. But positive Domar gap and primary surplus in some years has helped in reducing the debt-GSDP ratio. The presence of cointegration between revenue receipt and revenue expenditure; and revenue receipt and total expenditure implies that the state has been able to maintain fiscal sustainability during the period under consideration.
Keywords: H3; H6; 330; fiscal deficit; debt sustainability; Assam; cointegration; error correction mechanism